Evaluation of The Implementation of Storage Practices for Dry Foodstuffs in Relation to The Quality and Safety of Dry Foodstuffs - Jane Hasvita Sari; AASP Chandradewi; Luh Suranadi; Reni Sofiyatin (Poltekkes Kemenkes Mataram, 2026)
Background: The storage of dry foodstuffs that does not comply with standards can reduce quality and increase the risk of contamination, which impacts food safety. The appropriate arrangement of storage shelves is a key measure in maintaining the quality and safety of foodstuffs in nutrition service facilities. Research Purposes: To evaluate the implementation of appropriate storage shelving in relation to the quality and safety of dry foodstuffs at the Belanting Community Health Centre Nutrition Unit. Research Methods: This study is a descriptive observational study with a cross-sectional design. Data collection was conducted through direct observation of 10 types of dry foodstuffs before and after the implementation of appropriate storage racks. The aspects assessed included quality (colour, texture, aroma) and safety (biological, physical, and chemical contamination). Research Result: The results showed an improvement in food quality from 40% to 80%, and an improvement in safety from 20% to 90%. These positive changes occurred following the implementation of storage racks that met standard criteria, such as the use of appropriate materials, a closed design, cleanliness of the racks, non-stacked placement of items, and separation of items from sources of contamination. Conclusion: The implementation of appropriate storage racks plays a crucial role in improving the quality and safety of dry foodstuffs. This demonstrates that a good storage system needs to be consistently applied to ensure food quality and safety in nutrition facilities.